The Effect of IL-4 Gene Polymorphisms on Cytokine Production in Patients with Chronic Periodontitis and in Healthy Controls - Bartova, Jirina; Borilova Linhartova, Petra; Podzimek, Stepan; Janatova, Tatjana; Svobodova, Kazi; Fassmann, Antonin; Duskova, Jana; Belacek, Jaromir; Izakovicova Holla, Lydie (Mediators of Inflammation, 2014)
Chronic periodontitis (CP) is an inflammatory disease of the teeth-supporting tissues in which genetic predisposition, dental plaque bacteria, and immune mechanisms all play important roles. The aim of this study was to evaluate the occurrence of IL-4 gene polymorphisms in chronic periodontitis and to investigate the association between polymorphisms and cytokines production after bacterial stimulation. Sixty-two subjects (47 CP patients and 15 healthy controls) with detected two polymorphisms in the IL-4 gene (-590C/T and intron 3 VNTR) were examined. Production of cytokines (IL-1α, IL-1β, IL-4, IL-5, IL-6, IL-10, IL-17, TNFα, INFγ, and VEGF) was studied after in vitro stimulation of isolated peripheral blood by mitogens (Pokeweed mitogen, Concanavalin A), dental plaque bacteria (Aggregatibacter actinomycetemcomitans, Tannerella forsythia, Porphyromonas gingivalis, and Prevotella intermedia), and Heat Shock Protein (HSP) 70 by the Luminex multiplex cytokine analysis system. The results were correlated with IL-4 genotypes in patients with CP and healthy controls. The mononuclear cells isolated from peripheral blood of CP patients with selected IL-4 polymorphisms significantly altered the production of IFNγ, IL-10, IL-1β, IL-1α, TNFα, and IL-6 after stimulation by HSP 70 or selected bacteria (from P<0.001 to P<0.05). IL-4 gene polymorphisms may influence the function of mononuclear cells to produce not only interleukin-4 but also other cytokines, especially in patients with CP.